Secondary Modeling and Strain Variability of Listeria monocytogenes Isolated from Seafood and Clinical Samples at Various Environmental Conditions Using High-Throughput Turbidity Method - Abdollahzadeh, Esmail; Hosseini, Hedayat; Ojagh, Seyed Mahdi; Koushki, Mohammad Reza; Ansari Moghaddam, Lila (Applied Food Biotechnology, 2021)
Background and Objective: Variability of foodborne pathogens plays important roles in microbial risk assessment. In the present study, kinetic behaviors of seven Listeria monocytogenes and two Listeria innocua strains from various sources were assessed at various pH (4.5, 5.0, 5.5, 6.8 and 7.0) and salinity (0.5, 2.5, 3.5, 5, 7 and 10% NaCl). Material and Methods: Maximum specific growth rates (µmax) were assessed using Bioscreen C (time-to-detection method). Nearly 1500 curves were produced for Listeria monocytogenes and Listeria innocua strains and secondary models were developed for the bacteria as a function of NaCl, pH, temperature and undissociated lactic acid concentrations. Results and Conclusion: Variability of µmax enhanced as the growth environment became unfavorable. Coefficient of variation of µmax in Listeria monocytogenes strains were 6.5 and 20% at 0.5 and 7.5% NaCl (pH 7.26), respectively. After selecting the most robust strain, models demonstrating relationships between the growth rate and environmental conditions (NaCl, pH and undissociated form of lactic acid) were generated using Origin 2018 Software and polynomial and nonlinear surface fitting. In conclusion, intraspecies variability of the growth kinetic behaviors and developed models based on the worst case (e.g., the most robust Listeria monocytogenes strain) include important uses in food industries. Conflict of interest: The authors declare no conflict of interest.